Ablution Skills in Early Childhood: The Effect of Big Book Media - T. Idris; Arsyizahma Wita; Elvi Rahmi; Jhoni Warmansyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine the effectiveness of big book media on early childhood ablution skills. This study uses a quantitative approach with experimental methods with a pre-experimental research design type one group pretest-posttest design. The research sample amounted to 14 children. The data collection technique used a checklist for ablution skills. Data analysis technique using a t-test. The results showed that the average child’s ablution skills increased from the pre-test to 10.85, after being given big book media treatment, there was an increase from the average post-test result to 30.21. This is also reinforced by the results of hypothesis testing at a significant level of five percent, which got a t-count of 36.39 greater than the t-table. It can be said that the use of big book media is effective in improving early childhood ablution skills.